The Yersinia Yop virulon, a bacterial system to subvert cells of the primary host defense - Cornelis, G R (Folia microbiologica, 1998)
The Yop virulon enables yersinias (Yersinia pestis, Y. pseudotuberculosis and Y. enterocolitica) to survive and multiply in the lymphoid tissues of their host. It is an integrated system allowing extracellular bacteria to communicate with the host cell's cytosol by injection of effector proteins. It is composed of four elements: (1) a contact or type III secretion system called Ysc, devoted to the secretion of Yop proteins. This secretion apparatus, made of some 22 proteins, recognizes the Yops by a short N-terminal signal that is not cleaved off during secretion; (2) a system designed to deliver bacterial proteins into eukaryotic target cells. This system is made of YopB, YopD and LcrV; (3) a control element (YopN) and (4) a set of effector Yop proteins designed to disarm these cells or disrupt their communications (YopE, YopH, YopM, YpkA/YopO, YopP). The whole virulon is encoded by a 70-kb plasmid called pYV. Transcription of the genes is controlled both by temperature and by contact with a eukaryotic cell.
Keywords: Bacterial Outer Membrane Proteins; membránové proteiny; cytotoxické proteiny tvořící póry; Membrane Proteins; infekce yersiniemi; proteiny vnější bakteriální membrány; antigeny bakteriální; Antigens, Bacterial; Bacterial Proteins; zvířata; Humans; Protein Tyrosine Phosphatases; tyrosinfosfatasy; bakteriální proteiny; Yersinia; Yersinia Infections; lidé; Pore Forming Cytotoxic Proteins; Animals